Penyuluhan Bahan Tambahan Makanan Berbahaya Bagi Kesehatan Di SDN 200514 Desa Labuhan Labo - Diningsih, Ayus; Harahap, Olivia Feby Mon (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
The use of food additives (BTP) in the food production process needs to be watched out together, both by producers and by consumers. The impact of its use can have positive or negative consequences for society. Deviation in its use will endanger us together, especially the younger generation as the successor of nation development. This community service program aims to provide knowledge to students about food additives that are harmful to health and encourage students to consume foods that do not contain harmful chemicals. The target of the extension activities is the students of SDN 200514 in Labuhan Labo Village. Based on preliminary investigations, students did not know the dangers of food containing hazardous chemicals such as rhodamine B dye, borax preservative, MSG flavoring and artificial sweeteners. It cannot be denied that everyone, especially schoolchildren, really likes food snacks. Therefore, traders strive to give children an attractive appearance and taste by using certain ingredients regardless of safety. Therefore, it is necessary to carry out activities that include counseling about food additives that are harmful to health. This activity has contributed to improving the level of public health, especially for children to adolescents since they were in elementary school.